Design and fabrication of removable container trolley - Amar Reza, Mohammad Firdaus (2007)
The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. Manufacturing is a process of converting raw material into product. It can be described the transformation of materials into items of greater value by means of one or more processing and/or assembly operations. This project is about designing and fabricating the Removable Container Trolley that can be used to helps people transporting load items more efficiently. The main objective in this project is to design a Removable Container Trolley. This project involves the process of designing the trolley by considering the shape. functionality. portability and the manufacturing cost for people to use it. The material of this design is easy to gain it. because it only using rectangular hollow steel and circular hollow steel. So that the method joining that can be compatible in assembled this trolley is welding processes. In assembled the wheel. fastening method is the best chosen because it's only use bolt and nut to bind the wheel with the base of this trolley. This project also required analysis to make sure the strength of the product to ensure the safety for the user indeed of publishing. After all the process had been done. this trolley may help us to understand the fabrication and designing process that involved in this project.